Peran Ustadz Ashbiran Karim Dalam Menyiarkan Agama Islam Di Gunung Sindur Bogor Tahun 2016-2020 - Ayuni Zahra (Priangan: Journal of Islamic Sundanese Culture, 2025)
This study examines the role of local Ulama in remote areas, namely, Ustadz Ashbiran Karim or better known as Abi Karim in broadcasting Islam in the Gunung Sindur Region, Bogor in 2016-2020. This study aims to reveal the role and progress of Ustadz Ashbiran Karim in broadcasting Islam in the Gunung Sindur Region, Bogor. In order to obtain valid data, the method used in this research is the historical research method, which is a systematic procedure or technique based on the principles and rules of historical science. The technique in question includes several steps, including: topic selection, source selection (heuristics), internal and external criticism (verification), data analysis and interpretation (interpretation), as well as presentation in written form (historiography). This article attempts to explain the role of Ustadz Ashbiran Karim in dakwah Islamic religion in the Mount Sindur Region of Bogor as a pillar of building national integration. Ustadz Ashbiran Karim broadcasts Islam by preaching in various places by developing one's character first. With this writing, it is hoped that future generations of Muslims will be able to think based on the Qur'an.Keywords: Islam, Da'wah, Bogor.